A new species of Cyrtodactylus (Sauria: Gekkonidae) from Pulau Tioman, Malaysia - Das, I.; Jim, Lim Liang (National University of Singapore, 2000)
A new species of Cyrtodactylus is described from Pulau Tioman, an island off the east coast of Peninsular Malaysia. The new species can be differentiated from congeners from south-east Asia in showing the following combination of characters: medium-sized Cyrtodactylus (SVL to 83.2 mm); rostral partially divided by rostral groove, contacted posteriorly by two nostrils and two semi-circular supranasals; pectoral and abdominal scales smooth, rounded, semi-circular, imbricate; no preanal groove, a distinct preanal depression; sharp boundary between small scales on posterior surface of thighs and larger ones on ventral surface of thighs; tail without lateral denticles or tubercles forming whorls or segments; supralabials (to midorbit position) 8-11; infralabials 9-11; midventral scale rows at belly to lowest row of tubercles 36-40; lamellae under toe IV 20-22; preanofemoral pores 19; and dorsal pattern comprises four pale yellow transverse bands, each narrower than the intervening pale brown areas, edges with dark brown, and a pale yellow nuchal loop joining posterior edges of eyes